If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + 7 = a + 10 Reorder the terms: 7 + 4a = a + 10 Reorder the terms: 7 + 4a = 10 + a Solving 7 + 4a = 10 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 7 + 4a + -1a = 10 + a + -1a Combine like terms: 4a + -1a = 3a 7 + 3a = 10 + a + -1a Combine like terms: a + -1a = 0 7 + 3a = 10 + 0 7 + 3a = 10 Add '-7' to each side of the equation. 7 + -7 + 3a = 10 + -7 Combine like terms: 7 + -7 = 0 0 + 3a = 10 + -7 3a = 10 + -7 Combine like terms: 10 + -7 = 3 3a = 3 Divide each side by '3'. a = 1 Simplifying a = 1
| -3x(x^2-4)=9 | | 13/4+4y=8y-1/2 | | 0.11k+1.25=2.49 | | -27=-5-2n | | (3x-1)(3-x)+4x^2+19=0 | | 2a+9+5a= | | 5(-2+x)=6x-.2 | | C^2-4c+4= | | 3.14(2)+d=5(3.14) | | 8+2y-6=9y+7-6y | | C^3-4c+4= | | 3-6x=5x+25 | | 4x=(540/6) | | 2.3(x-6)=2 | | 9(x-15)=6(x-10)+10 | | 9n-5+2n= | | 7m+6.8m= | | 3/4(4x-12)=3(9-7x) | | A=5/u-d | | 3.3(x-6)=2 | | 58-(4x+4)=4(x+9)+x | | 12x=9x+4 | | -22=v/3-4 | | 15y-6y= | | 5/7x-6=13 | | 1=-y/4-6 | | 9w^2+12wg+4g^2= | | 2/3x-6=7 | | 52/3k=-35/3k^2-4 | | 12/6x3-5 | | -7+4u=-3 | | 12x-3=2+2x |